Experimental training in molecular pharmacology education based on drug-target interactions - Luna Ge; Kai Cheng; Yuang Zhang; Junling Li; Wei Chen; Guanhua Song; Lin Wang (Wiley, 2023)
Abstract Introduction Drug development has been challenged by the dual drawbacks involving unpredictable disease outcomes and drug resistance, which has placed greater demands on pharmacology education. Molecular pharmacology, as a frontier crossover field of pharmacology, focuses on the research of new drugs and targets. However, due to the lack of a systematic experimental training system, molecular pharmacology has not made a corresponding contribution in promoting the training of innovative talent in pharmacology. We aim to establish an experimental training program suitable for molecular pharmacology to improve students' ability to engage in drug development in future. Methods Based on the feasibility of drug-target projects, a comprehensive training program containing molecular docking, target stability experiment, and fluorescent probe detection of protein expression in living cells and mice was conducted among 20 pharmacy graduate students. The experimental training was assessed by the experimental training report and the student recognition questionnaires. Results All 20 students mastered the experimental principles and operations required for the training program. The experimental reports proved that the students were in good command of the experimental principles, operations and applications. The results of the Likert questionnaire indicated that the training program promoted the understanding of the drug research process and increased motivation to learn. Conclusion The designed experimental training program has a positive effect on the training of pharmacology talents, and can be implemented as a part of molecular pharmacology education.